Executive Committee Minutes 2015-03-26 - Academic Senate:::::::::
Agenda approved. Minutes of 3/5/15 – Approved. Chair Report. Provost Report. Statewide Senator Report. Revision to the Biology BA and BS approved for Senate consent calendar. Honorary Degree Committee. Vice Chair Report. Vice President of Administration and Finance Report. Senate feedback on proposed Hospitality revision approved for Senate agenda. Posthumous degree request for Francis Lynch approved for Senate agenda. Vice President of Student Affairs Report. EPC Report. FSAC Report. SAC Report. CFA Report. Associated Students Report. Ex Com rep to SEC Report. Senate agenda approved. Good of the Order.